On the Turkish species of Sunius. VII. Five new micropterous species from western Anatolia and additional records (Coleoptera: Staphylinidae, Paederinae). - Assing, Volker (Contributions to Entomology = Beiträge zur Entomologie, 2006)
Five micropterous and apparently locally endemic species of Sunius Curtis, 1829 from western Anatolia are described and illustrated: S. bozdagensis sp. n. (Izmir: Boz Dalar), S. pinniger sp. n. (Izmir), S. fortespinosus sp. n. (Aydn/Izmir: Aydn Dalar), S. sexspinosus sp. n. (Mula), and S. pinnatus sp. n. (Manisa). Their distributions are mapped. Additional records are presented for two species, among them the first record of S. phasianus (Bordoni) from Iran. 25 Sunius species are now known from Turkey, including one name of doubtful identity. An updated key to the Turkish representatives of the genus is provided.KeywordsColeoptera, Staphylinidae, Paederinae, Sunius, Palaearctic region, Turkey, Iran, taxonomy, new species, new records, distribution, endemism.Nomenclatural Actsbozdagensis Assing, 2006 (Sunius), spec. n.fortespinosus Assing, 2006 (Sunius), spec. n.pinnatus Assing, 2006 (Sunius), spec. n.pinniger Assing, 2006 (Sunius), spec. n.sexspinosus Assing, 2006 (Sunius), spec. n.